“Estimulación Mamaria en el periodo crítico del pppuerperio inmediato para la involución Uterina. Hospital I-IPSS. Moyobamba – 1994” - Pizango Solsol, Llerme (1994)
Currently, in our midst, pregnant are one of the most vulnerable within the problems of health, since our country is going through a socio-cultural and economic crisis. So it is necessary to avoid any possible expenditure during the childbirth attendance; in its different phases, which should be conducted within the physiological process. Of labour basically consists of three periods, importing us to understand our students. io, to part.i r of the third period, which begins after the birth of the niAo and ends with the expulsion of the placenta and fetal membranes. This corresponds to the period of detachment and E. >:-: drive dr-: the pl ~.! lcenta. (4,:; 3, 34, 38). AlgLmos obstetricians referred to a fourth period of confinement that lasts approximately an hour during which shrinkage and contraction of the myometrium with thrombosis vessel controlling hemorrhage at the level of the implantation of the placenta area. (33) the place...